Pharmacokinetics of Dapaconazole, A Novel Antifungal Agent, in Beagle Dogs and Inhibition of Cytochrome P450 Family 51 - Palo, Juliana S.; de Freitas, Noedi L.; Silva, Samuel G.N.e; Rojas-Moscoso, Julio A.; Zaminelli, Tiago; Lescano, Caroline H.; D. Mendes, Gustavo; De Nucci, Gilberto (Anti-Infective Agents, 2018)
Objectives: Pharmacokinetics of dapaconazole and inhibition of cytochrome P450 family 51. Methods: Pharmacokinetics of dapaconazole, a novel imidazolic antifungal compound, was studied in male beagle dogs following intravenous (1, 2 and 20 mg/kg) and oral (20 mg/kg) administration. Results: Oral bioavailability was calculated to be 97.3%. The elimination half-life (t½) after intravenous administration was 2.1-2.5 h, the total body clearance was 2.5-4.2 L/h/kg and the apparent volume of distribution was 9.0-14.4 L/kg. Dapaconazole caused concentration-dependent inhibition of cytochrome P450 family 51 (CYP51) activity with an IC50 of 1.4 ± 0.3 μM (mean ± SEM, n=3), compared to that of ketoconazole (IC50 = 1.2 ± 0.6 μM, n=3). Conclusion: Results indicate that dapaconazole could be a potentially useful drug for systemic administration.
Keywords: mass spectrometry